The economic impact of two-stage knee arthroplasty revisions: a projection for a specialized health center in Türkiye - Yurtbay, Alparslan; Ersoy, Ahmet; Şay, Cahit Şemsi; Say, Ferhat (The European Research Journal, 2024)
Objectives: The increase in the number of arthroplasty surgeries worldwide also leads to an increase in revision surgeries. This study examines the costs of primary and revision arthroplasty treatments in a tertiary university hospital’s orthopedics and traumatology clinic. It also explores the impact of revision surgeries on the healthcare system. Methods: Seventy-six patients who had total knee arthroplasty at a university hospital between 01.01.2017 and 30.09.2022 were included in the study. The patients were divided into three groups: primary (n=25), aseptic reasons one-stage revision (n=27), and septic reasons two-stage revisions (n=24). For each patient included in the study, detailed documents regarding medical supplies, anesthesia, operating room, intensive care, consultation, medicine/serum, medical treatment, laboratory, blood and blood products, microbiology, radiology, food, bed, and attendant fees were provided separately by the hospital purchasing and statistics departments. Results: When comparing the costs of primary, one-stage revision, and two-stage revision surgeries, the average costs were 5689 Turkish Lira (₺), 8294.97 ₺, and 40919.67 ₺, respectively. In patients with septic reasons, the group that underwent two-stage revisions had significantly higher costs than the aseptic group in terms of surgery time, hospital stay duration, medication, treatment, surgery, anesthesia, intensive care, laboratory tests, imaging, blood center services, consultations, visits, meal expenses, and invoiced amount (P<0.001). Conclusion: Preventing and treating periprosthetic infections is costly and challenging. We need more research to develop effective protocols and reduce costs. As the number of patients undergoing knee arthroplasty is expected to rise, healthcare systems must ensure the sustainability of public financial resources, especially in public university hospitals.